Human Rights Court and Truth Reconciliation Commission for the Settlement of Human Rights in Indonesia - Junaedi, Junaedi (Indonesian Comparative Law Review, 2018)
The law on human rights court has brought the new hopes for certain people have suffered because of the human rights violation happened in the past government (before the law enacted in the years of 2000). The demand of justice has been made by victims, the families of victims and other sympathetic parties by bringing those who have violated human rights in the past. The demand for justice does not only focus on human rights violations, which occurred in the past but also similar human rights violations that will occur in the future. The existence of a permanent Human Rights Court seems to imply that human rights will be upheld and protected. The resolution of past human rights violations via a conflict approach is preferable for the national reconciliation. The resolution of past human rights violations through extra-judicial organizations is an advanced step towards resolving the case, whereas a conflict approach can be used to settle the case.Â  The existence of the Human Rights Law provides a new frontier in implementing the principle of restorative justice in the approach of case settlement. It is hoped that such restorative justice can create a political balance between the past and the future.